Assessing the accuracy of intracameral phenylephrine preparation in cataract surgery. (October 2018) - Guthrie, Stuart; Jensen, Thomas; Hartley, Richard C.; Ramaesh, Kanna; Lockington, David
Abstract Purpose Unpreserved phenylephrine is often used as an off-licence intracameral surgical adjunct during cataract surgery to assist with pupil dilation and/or stabilise the iris in floppy iris syndrome. It can be delivered as a neat 0.2 ml bolus of either 2.5 or 10% strength, or in a range of ad-hoc dilutions. We wished to assess the accuracy of intracameral phenylephrine preparation in clinical practice. Methods Phenylephrine 0.2 ml was analysed both neat (2.5 and 10%) and in diluted form (ratio of 1:1 and 1:3). Samples were analysed using the validated spectrophotometric method. Results A total of 36 samples were analysed. The standard curve showed linearity for phenylephrine (R 2  = 0.99). Wide variability was observed across all dilution groups. There was evidence of significant differences in the percentage deviations from intended results between dilutions (p  < 0.001). Mean percentage deviation for 1:3 dilution was significantly greater than neat (p  = 0.003) and 1:1 dilution (p  = 0.001). There was no evidence of a significant difference between 1:1 and neat (p  = 0.827). Conclusions Current ad-hoc dilution methods used to prepare intracameral phenylephrine are inaccurate and highly variable. Small volume 1 ml syringes should not be used for mixing or dilution of drug. Commercial intracameral phenylephrine products would address dosage concerns and could improve surgical outcomes in cases of poor pupil dilation and/or floppy iris syndrome.